2007
DOI: 10.1562/2006-07-25-ra-982
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Sensitized Photodegradation of Uracil-Modeling the Fate of Related Herbicides in Aqueous Environments†

Abstract: The dye-sensitized photodegradation of uracil (UR), the parent compound of several profusely employed herbicides, has been studied as a model of their environmental fate. In order to mimic conditions frequently found in nature, aqueous solutions of UR have been irradiated with visible light in the presence of the natural sensitizer riboflavin (Rf). The results indicate that UR is photostable in acid media, but is quickly degraded in pH 7 or pH 9 solutions, where singlet molecular oxygen [O2(1Delta(g))] and, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Besides that, it has been reported that Rf is present in natural waters and could participate in the degradation of different organic pollutants , and in this case, it is expected that the reaction of 3 Rf*, O 2 ( 1 Δ g ) or O2· is not a significant process in the degradation of IXF since, although it is a continuous process, it would not compete with the hydrolysis rate at pH close to 7.…”
Section: Discussionmentioning
confidence: 96%
“…Besides that, it has been reported that Rf is present in natural waters and could participate in the degradation of different organic pollutants , and in this case, it is expected that the reaction of 3 Rf*, O 2 ( 1 Δ g ) or O2· is not a significant process in the degradation of IXF since, although it is a continuous process, it would not compete with the hydrolysis rate at pH close to 7.…”
Section: Discussionmentioning
confidence: 96%
“…It is interesting to compare the kinetic constants for SFU at pHs 7 and 12 with those of uracil previously published. 20 The values of these constants (Table 2) suggest that the presence of the sulfamino-group as a substituent in the uracil moiety exerts an activating power on its nucleus. This is based on the increase of the constants for the global and for the reactive processes in the interaction with SFU compared to the uracil in alkaline medium.…”
Section: Interaction Between Sfu and Rf-electronically Excited Statesmentioning
confidence: 99%
“…This degradation happens in the presence of either dissolved organic matter or other reactive species that can be formed in natural surface waters. [17][18][19] Regarding the uracil molecule, which is part of the SFU structure, it has been reported by our group 20 that its sensitized photodegradation takes place with the involvement of reactive oxygen species (ROS) such as singlet molecular oxygen [O 2 ( 1 Δ g )] and superoxide radical anion (O 2…”
Section: Introductionmentioning
confidence: 99%
“…A daylight‐absorbing pigment of particular interest is the naturally occurring vitamin B 2 , riboflavin (Rf). The vitamin is endogenously present in living organisms, and has been postulated as a possible sensitizer for the in vivo photo‐oxidative degradation of proteins, puric bases and fatty acids, among other biologically relevant substrates (8–13).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with puric bases showed that Rf‐photosensitized processes could be responsible for photodamaging of DNA (14). Recently we reported kinetic studies on the Rf‐sensitized photo‐oxidation of ur, uric acid, xanthine and hypoxanthine in aqueous solution, mediated by ROS (9,15). The aerobic light‐induced interaction of Rf with proteins is well known to occur through ROS‐mediated oxidation of one or several of the five photo‐oxidizable AAs: tyr, trp, methionine, histidine and cysteine (16–19).…”
Section: Introductionmentioning
confidence: 99%